2009
DOI: 10.1002/pssb.200982267
|View full text |Cite
|
Sign up to set email alerts
|

Electrophysical properties of multiwalled carbon nanotubes with various diameters

Abstract: We have investigated temperature s(T) and magnetic field s(B) dependences of the conductivity s of multiwalled carbon nanotubes (MWNTs) with different average outer diameter d. From the experimental data we have separated the quantum corrections to s(T) and s(B). We have discovered that only quantum corrections for interaction electrons (QCIE) to s(B) take place. It is associated to the absence of the bulk formations of amorphous carbon in produced MWNTs. From the data of QCIE we have estimated the constant of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
10
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 15 publications
3
10
0
Order By: Relevance
“…However, the spectrum of nanotubes with a diameter 20 nm shows a considerable difference of intensities I D / I G . It means that the thicker tubes are less defective that correlated with the previously obtained results with an independent electophysical study of MWNTs with various diameters 4. These data also are confirmed by the HRTEM measurements.…”
Section: Resultssupporting
confidence: 88%
“…However, the spectrum of nanotubes with a diameter 20 nm shows a considerable difference of intensities I D / I G . It means that the thicker tubes are less defective that correlated with the previously obtained results with an independent electophysical study of MWNTs with various diameters 4. These data also are confirmed by the HRTEM measurements.…”
Section: Resultssupporting
confidence: 88%
“…Positive magnetoconductivity of MWNTs (Fig. 4B) can be explained within quantum corrections for electron interactions 13.…”
Section: Resultsmentioning
confidence: 89%
“…It was revealed that MWNTs diameter influences the type of conductivity behavior, namely small diameter (8–10 nm) MWNTs demonstrate the temperature dependence of conductivity as σ ( T ) ∼ exp( T −1/2 ) below about 20 K, which can be described within theory of Coulomb blockade or quasi one‐dimensional variable range hopping conductivity, while thicker MWNTs (20–22 nm) demonstrate two‐dimensional quantum corrections to conductivity below ∼20 K (see the inset in Fig. 4A σ ( T ) ∼ ln T ) 13. Figure 4A shows the increase of angle of curve inclination with the increase of annealing temperature in axes σ ( T )/ σ (293) − T for CE‐type MWNTs.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…The temperature dependences of the conductivity σ ( T ) and magnetoconductivity σ ( B ) were measured by four point probe technique. σ ( T ) in the temperature range of 4.2–300 K while σ ( B ) was measured in the field B range 0–6 T at 4.2 K 15–17. These data were used to characterize the defectiveness of MWNT structure.…”
Section: Experimental and Methodologymentioning
confidence: 99%